Promoting Enquiry Skills in Trainee Teachers within the Context of the University Ecological Garden - Lourdes Aragón; Beatriz Gómez-Chacón (Education Sciences, 2022)
One of the objectives of science teaching and learning is to achieve quality science education, which involves improving initial teacher training. The use of methodologies that promote learning in science, such as the enquiry-based learning strategy, are encouraged. It is also necessary to provide appropriate contexts that give meaning to the investigation conducted, and arouse the students’ interest. The purpose of this study is to identify the skills related to the enquiry competency that future pre-school teachers acquire after carrying out investigations using the University Ecological Garden as a context. To undertake this study, a non-experimental quantitative methodology was developed based on the application of two instruments: the New Practical Test Assessment Inventory (NPTAI), based on the Practical Test Assessment Inventory, and the trainee teachers’ Enquiry Competency Level (ECL), adapted for the present work. Thirty-seven group reports were analysed and recoded to establish five levels of enquiry competency. A predominance of students with a high level of enquiry competency as opposed to "pre-scientific" and "unscientific" lower levels was observed. The results allowed us to explore the role of the teacher in the monitoring process during the strategy, the context used, and the main difficulties encountered in the implementation of the strategy.